(untitled) - Price, John Ellis (Boston, MA., 2003)
College Accounting continues to offer its trademark short learning segments followed by self-review questions and answers. This book has been thoroughly revised and given a new visual design. The book also includes more real-world examples than ever, high-interest problems and activities, in-text help, classroom-tested features, and support for a variety of software packages. The new edition continues to be the most current and thorough text available, and provides solid coverage of accounting concepts and principles.
Keywords: Accounting